2011
DOI: 10.1021/la200480d
|View full text |Cite
|
Sign up to set email alerts
|

Photoinduced Electron Transfer and Fluorophore Motion as a Probe of the Conformational Dynamics of Membrane Proteins: Application to the Influenza A M2 Proton Channel

Abstract: The structure and function of the Influenza A M2 proton channel have been the subject of intensive investigations in recent years because of its critical role in the life cycle of the Influenza virus. Using a truncated version of the M2 proton channel (i.e., M2TM) as a model, here we show that fluctuations in the fluorescence intensity of a dye reporter that arise from both fluorescence quenching via the mechanism of photoinduced electron transfer (PET) by an adjacent tryptophan (Trp) residue and local motions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 18 publications
(41 citation statements)
references
References 37 publications
2
39
0
Order By: Relevance
“…While the current study does not provide any direct information about the structural nature of this step, it likely suggests that an additional conformational change, either at the sidechain (e.g., Trp41) or the backbone level, 8,22,29,31,40 or a transiently occupied proton diffusive state 32 is required to successfully relay a proton from His37 to the water at the C-terminal end of the channel, instead of a purely two-state equilibrium process proposed by the transporter model. 23 Interestingly, a recent single-molecule fluorescence study 55 on the M2TM channel showed that the Trp41 residue exhibits a slow conformational motion, on the timescale of ~500 μs. This slow motion, whose rate is similar to that of proton conduction, could potentially be the aforementioned conformational change required to deliver a proton from B to C.…”
Section: Resultsmentioning
confidence: 99%
“…While the current study does not provide any direct information about the structural nature of this step, it likely suggests that an additional conformational change, either at the sidechain (e.g., Trp41) or the backbone level, 8,22,29,31,40 or a transiently occupied proton diffusive state 32 is required to successfully relay a proton from His37 to the water at the C-terminal end of the channel, instead of a purely two-state equilibrium process proposed by the transporter model. 23 Interestingly, a recent single-molecule fluorescence study 55 on the M2TM channel showed that the Trp41 residue exhibits a slow conformational motion, on the timescale of ~500 μs. This slow motion, whose rate is similar to that of proton conduction, could potentially be the aforementioned conformational change required to deliver a proton from B to C.…”
Section: Resultsmentioning
confidence: 99%
“…One such “breath” of the transporter-like behavior of M 2 channels takes about 500 μs, and bound drug molecules occlude the channel to block its “breathing”. 202 Solid-state NMR studies later focused on how amantadine blocks the proton flux through the channel. Binding of amantadine suppresses proton exchange from His37 to the water within the channel upon reorientation of the His37 imidazole rings.…”
Section: The First Hit: Adamantane Derivatives As Antivirals and Amentioning
confidence: 99%
“…Thus, although the idea that DNA could have electronic conductivity appeared half a century ago [40], this idea received general attention 30 years later, from the experiments of Barton and co-workers [41,42], based on photoinduced electron transfer reactions. This type of reaction is also the main approach to explore the dynamics of some systems [43]. For these and other applications photoinduced electron transfer became currently interesting.…”
Section: Electron Transfer With Participation Of Excited Statesmentioning
confidence: 99%